Pengaruh Komunikasi dan Lingkungan Kerja terhadap Kinerja Pegawai dengan Motivasi sebagai Variabel Intervening pada PT. Pos Indonesia Kantor Regional I Medan - Nurmah Fudzah; Syaiful Bahri; Leylia Khairani (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2020)
The purpose of this study was to determine the effect of communication and work environment on employee performance with motivation as an intervening variable at PT. Regional Post-I Medan. The research sample was all employees at PT. Regional Post I Medan, amounting to 84 people. The partial test results that communication has no significant effect on motivation and the work environment has a significant effect on motivation. The second equation shows that communication has no and insignificant effect on employee performance, the work environment has a significant effect on employee performance and motivation has no and insignificant effect on employee performance. Meanwhile, simultaneous testing for the first equation is communication and work environment which have a significant effect on motivation. The second equation proves that communication, work environment and motivation have a significant effect on employee performance. The test using path analysis proves that motivation cannot be a variable that mediates between communication variables on employee performance and motivation cannot be a variable that mediates between work environment variables on employee performance.